FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS AUDIT YANG DILAKUKAN OLEH AUDITOR PEMERINTAH Studi Empiris pada Perwakilan BPK dan BPKP Provinsi Kalteng - Randy W Permana; Wahyu Manuhara Putra (Jurnal Riset AKuntansi dan Bisnis, 2016)
This study aims to analyze Factors Affecting Quality of Audit on Public Sector Auditor working on BPK and BPKP Representative of Central Kalimantan Province. Subjects in this study are the auditors who worked on representation BPK and BPKP Central Kalimantan Province. The samples in this study are 65 respondents whom selected based on total sampling. The analysis tool used is Multiple Linear Regression. The Study indicates the factors that affect quality of audit are independence, competence, experience, and risk errors. However, complexity of audit does not affect the quality of audits.